Analisis Dampak Bonus Demografi Terhadap Kesempatan Kerja di Propinsi Aceh - Uswatun Hasanah Hasanah; Dicky Armanda (Sekolah Tinggi Ilmu Administrasi Nasional, 2021)
It is estimated that between 2020-2035 Indonesia will encounter the peak of the demographic bonus. Aceh Province is one of the provinces in Indonesia that will experience this phenomenon. The demographic bonus is like a double-edged sword. On the one hand, it can be an opportunity and on the other, it can be a catastrophe. For this reason, the government's role in dealing with this phenomenon is urgently required. Policies that are able to stimulate the absorption of productive age workers are expected to be carried out by the government. The demographic bonus will truthfully be a bonus for the Indonesian citizens if the excess population of productive age can be employed in the right system. This study discusses the factors that affect employment opportunities, where job opportunities are one of the indicators of whether or not a country is optimal in taking advantage of the demographic bonus. The factors analyzed are the dependency ratio and the relationship between labor and employment opportunities. In this study, multiple linear regression analysis was used using secondary data of the time series type for the research period from 2010-2016. The results of this study indicate that there is a positive and significant effect between the number of workers on job opportunities. Besides, there is also a negative and significant influence between the dependency ratio on job opportunities.